A naturally degradable disposable tableware and a preparation method thereof
Patent Information
- Application Number
- CN202611265482.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-20
- Publication Date
- 2026-10-27
AI Technical Summary
但此类餐具存在如下不足:所采用的粘结剂或为化学合成胶黏剂,或为淀粉类粘结剂,前者使制品丧失”纯天然、全降解”的环保属性,后者粘结强度和耐水性较差,且通常还需配套使用化学防水剂、脱模剂等化工助剂,难以满足食品接触安全与全自然降解的双重要求
[0034](1)本发明的餐具原料全部由小麦蛋白、天然植物纤维及可选的天然树胶构成,生物基含量达 100%,制备过程为纯物理加工,不添加任何化学合成的粘结剂、防水剂、增塑剂及防腐剂,产品可在自然环境中完全降解,同时满足一次性餐具的环保要求与食品接触安全要求;
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of disposable tableware preparation technology, specifically to a biodegradable disposable tableware and its preparation method. Background Technology
[0002] The use of disposable tableware is enormous, and traditional plastic tableware is difficult to degrade, causing serious environmental pollution. Currently, most domestically produced disposable biodegradable tableware is made from polylactic acid (PLA), a biodegradable material. However, PLA products can only be processed under specific industrial composting conditions after use. This process consumes land resources and incurs various costs. A significant portion of discarded PLA tableware is not effectively disposed of, causing the same environmental pollution problems as non-biodegradable tableware. Furthermore, some countries and regions have already imposed restrictions on disposable tableware made of PLA. Therefore, developing disposable tableware made entirely from plant-based materials that can degrade in the natural environment is an inevitable direction that meets international and domestic environmental protection requirements.
[0003] Existing technologies include disposable tableware made from plant fibers as the matrix and molded with adhesives. However, such tableware has the following shortcomings: the adhesives used are either chemically synthesized adhesives or starch-based adhesives. The former causes the product to lose its "purely natural and fully degradable" environmental attributes, while the latter has poor bonding strength and water resistance, and usually requires the use of chemical waterproofing agents, release agents, and other chemical additives, making it difficult to meet the dual requirements of food contact safety and full natural degradation.
[0004] Wheat gluten (vitamin gluten) is a natural byproduct of wheat processing, possessing excellent adhesive, film-forming, and heat-curing cross-linking properties, and is a food-grade raw material. Using it as a binder for disposable tableware based on natural plant fiber holds promise for obtaining tableware products with strength, water resistance, and fully biodegradable properties without adding any chemical raw materials. However, during implementation, it was found that wheat gluten powder absorbs water rapidly and has strong viscosity; direct mixing with water easily leads to clumping and uneven humidification, resulting in localized adhesion failure. Furthermore, without using any chemical waterproofing agents or release agents, the product's water resistance, release properties, and crack resistance all need to be addressed. Summary of the Invention
[0005] The primary objective of this invention is to provide a biodegradable disposable tableware, which uses wheat protein as a binder and natural plant fiber powder as a matrix. All raw materials are plant-based, and no chemically synthesized binders, waterproofing agents, plasticizers, or preservatives are added during the preparation process. It is completely biodegradable.
[0006] Therefore, the present invention provides a biodegradable disposable tableware, which is made by molding from all-plant raw materials containing binder components and fiber components; the binder component is wheat protein powder, and the fiber component is natural plant fiber powder.
[0007] However, the following technical problems exist in the implementation of this basic solution:
[0008] (1) Wheat protein powder absorbs water quickly and has strong viscosity. It is easy to stick together and clump during the humidification process, resulting in uneven material humidity and insufficient local strength of the product after molding.
[0009] (2) Technical problems of insufficient water resistance and easy softening and deformation when exposed to hot water without the addition of chemical waterproofing agents;
[0010] (3) Technical problems such as the product being too brittle, the surface easily shedding powder, and cracking and deformation during the drying process;
[0011] (4) The large difference in specific gravity between wheat protein powder and natural plant fiber powder makes them prone to separation during dry mixing, resulting in a technical problem of uneven product composition.
[0012] (5) Technical problem of material sticking to the mold and difficult demolding during compression molding, while chemical release agents are not allowed.
[0013] Therefore, in order to solve the above-mentioned problems, the present invention adopts the following technical solution:
[0014] A biodegradable disposable tableware is made by compression molding from an all-plant-based raw material containing a binder component and a fiber component; the binder component is wheat protein powder, and the fiber component is natural plant fiber powder; by mass percentage, the wheat protein powder accounts for 25% to 60% of the raw material, and the natural plant fiber powder accounts for 40% to 75% of the raw material; the raw material does not contain chemically synthesized binders, waterproofing agents, plasticizers, or preservatives.
[0015] Preferably, the wheat gluten powder is wheat gluten powder with a protein content of not less than 75% and a particle size of 80-200 mesh. If the protein content is too low, the binding force is insufficient, requiring an increased dosage and resulting in poor economic efficiency; if the particle size is too coarse, the swelling is slow and the dispersion is uneven, while if it is too fine, it is prone to dust and clumping.
[0016] Preferably, by weight percentage, the wheat protein powder preferably accounts for 30% to 45% of the raw materials, and the natural plant fiber powder preferably accounts for 55% to 70%; more preferably, the wheat protein powder accounts for 35% to 40%, and the natural plant fiber powder accounts for 60% to 65%. When the wheat protein powder content is less than 25%, the binding force is insufficient, and the product is prone to powdering and breakage; when it is higher than 60%, the material is too sticky, making it difficult to maintain a loose state after spraying with water, and the cost increases, and the taste and smell deteriorate.
[0017] Preferably, the natural plant fiber powder is selected from one or more of bamboo powder, wood powder, straw powder, rice husk powder, wheat bran powder, bagasse powder, and coconut shell powder, with a particle size of 20 mesh to 500 mesh. Bamboo powder with low water absorption is preferred.
[0018] Preferably, the natural plant fiber powder is a blend of coarse and fine fiber powders. The coarse fiber powder has a particle size of 20-100 mesh, and the fine fiber powder has a particle size of 100-500 mesh, with a mass ratio of 1:5 to 1:1. The fine fiber powder fills the gaps between the coarse fiber powders, making the molded blank more compact, thereby improving product strength, surface finish, and reducing powder shedding. The coarse fiber powder forms the skeleton, preventing product shrinkage and deformation.
[0019] Preferably, the raw material further comprises 5% to 15% natural gum powder, which is gum arabic powder and / or gum arabic powder. Natural gum, after absorbing water and swelling, has a thickening and toughening effect, introducing flexible components into the protein bonding network, significantly improving the product's brittleness and reducing drop breakage rate; however, when its content exceeds 15%, the product's hygroscopicity increases, while its water resistance decreases.
[0020] The finished disposable tableware has a moisture content of 3% to 6%, a bio-based content of 100%, and can be completely degraded in the natural environment.
[0021] The present invention also provides a method for preparing the above-mentioned disposable tableware, comprising the following steps:
[0022] S1. Ingredient Mixing: Weigh wheat protein powder, natural plant fiber powder and optional natural gum powder according to the formula, mix them evenly in a dry state to obtain a mixed powder;
[0023] S2. Spray humidification: Spray water onto the mixed powder while stirring until the material moisture content is 15%~30%, and the material is in a soft state that can be formed into a ball and dispersed when lightly pressed.
[0024] S3. Compression molding: The humidified material is metered and added into the product mold and pressed to shape it. The molding pressure is 50~150 tons.
[0025] S4. Heating and curing: Keep warm at 130℃~160℃ for 60 s~120 s to allow the wheat protein to cross-link and solidify, binding the natural plant fiber powder together.
[0026] S5. Drying: After demolding, the product is dried with hot air until the moisture content is 3%~6%. Then, it is inspected, packaged, and sterilized to obtain the finished product.
[0027] Preferably, in step S2, the spray humidification is performed intermittently in 2-4 stages, with stirring continued for 30-120 seconds after each spray before the next spray. After spray humidification, stirring continues for 20-30 minutes, and the material is then allowed to stand and swell for later use. Wheat protein powder requires a certain amount of time to absorb water and swell. Spraying all the water at once will cause the surface powder to absorb water and clump together instantly, while the interior remains dry powder. Segmented intermittent spraying combined with continuous stirring allows water to penetrate evenly layer by layer. Standing and swelling ensures that the moisture inside and outside each particle is fully balanced, and the material as a whole reaches a uniform "clump-and-disperse" state, ensuring uniform bonding strength of all parts of the product after molding. Preferably, the atomized particle size of the spray water is no greater than 50μm, and the water temperature is 20℃-60℃. Using warm water at 30℃-50℃ can promote uniform swelling of wheat protein powder without causing local overheating and denaturation.
[0028] Preferably, in step S1, wheat protein powder is first premixed with fine-grained natural plant fiber powder, which accounts for 10% to 30% of the total natural plant fiber powder, to form a masterbatch. Then, the masterbatch is mixed evenly with the remaining raw materials. Wheat protein powder and fiber powder have a large difference in specific gravity, and if they are directly mixed, they are prone to stratification due to vibration during the conveying process. After being made into a masterbatch, the wheat protein powder is adsorbed and diluted by the fine fiber powder, and the dispersion stability is significantly improved, ensuring that the composition of each batch of material is uniform.
[0029] Preferably, in step S3, the product mold is preheated to 100℃~140℃ before material feeding. After the mold is preheated, the surface moisture of the material in contact with the mold evaporates rapidly, forming an instantaneous vapor isolation layer between the blank and the mold cavity, achieving physical demolding without the need for any chemical release agents, and the product surface is smooth.
[0030] Preferably, in step S4, the curing temperature is 145℃~150℃. Within this temperature range, wheat protein undergoes sufficient thermal denaturation and intermolecular cross-linking (including disulfide bond recombination), transforming from a swellable powder into an insoluble solidified network, forming a dense protein solidified layer on the surface of the green body. This solidified layer serves as a natural water-resistant barrier for the product, allowing it to withstand hot water immersion without softening or deformation without the addition of any chemical waterproofing agents. Below 145℃, protein solidification is insufficient, resulting in poor water resistance; above 150℃, plant fibers are prone to charring and discoloration, causing the product to develop an off-odor.
[0031] Preferably, in step S5, the hot air drying is carried out in two stages: first, drying at 55℃~75℃ until the product moisture content is 8%~12%, and then drying at 85℃~110℃ until the product moisture content is 3%~6%. The blank after demolding has a high moisture content. If high temperature and rapid drying are used directly, the surface moisture will evaporate rapidly, the surface layer will shrink and harden first, and the internal moisture will be hindered from migrating outward, making the product prone to cracking and warping. Passing through a slow drying section at a lower temperature first makes the internal and external moisture gradient more gradual, and then passing through a fast drying section at a higher temperature to remove residual moisture can significantly reduce the cracking rate and deformation rate and improve the yield.
[0032] When the disposable tableware is a straw, steps S3 and S4 are replaced by: extruding and curing the humidified material through a screw extruder, cutting off the extruded material, dehydrating it with hot air, and then proceeding to step S5.
[0033] By implementing the above technical solution, compared with the prior art, the present invention has the following beneficial effects:
[0034] (1) The tableware raw materials of the present invention are all composed of wheat protein, natural plant fiber and optional natural gum, with a bio-based content of 100%. The preparation process is a pure physical process, without adding any chemically synthesized binders, waterproofing agents, plasticizers and preservatives. The product can be completely degraded in the natural environment, while meeting the environmental protection requirements and food contact safety requirements of disposable tableware.
[0035] (2) By utilizing the characteristics of wheat protein to cross-link and solidify under heat, an insoluble protein bonding network and a dense solidified surface layer are formed during the ripening process at a specific temperature. This gives the product both bonding strength and water resistance without the addition of chemical waterproofing agents, thus overcoming the technical limitation that existing plant fiber tableware must be waterproofed by adding chemical waterproofing agents.
[0036] (3) The combination of segmented intermittent spray humidification and static proofing solves the problem of uneven humidification caused by the rapid water absorption and easy clumping of wheat protein powder, resulting in uniform strength of all parts of the product; the combination of coarse and fine granulated fiber powder and natural resin toughening results in a dense, smooth, non-powder-shedding, and drop-resistant product; two-stage hot air drying significantly reduces cracking and deformation rates; masterbatch premixing solves the problem of powder stratification; and mold preheating achieves physical demolding without chemical release agents. The above solutions work together to achieve a high yield and stable product quality in the industrial implementation of the basic solution. Detailed Implementation
[0037] The present invention will be further described below with reference to the embodiments. The following embodiments are only used to illustrate the technical solutions of the present invention, and are not intended to limit the scope of protection of the present invention; any modifications, equivalent substitutions and improvements made within the concept and principles of the present invention should be included within the scope of protection of the present invention.
[0038] In all embodiments, the wheat gluten powder used was food-grade wheat gluten (80% protein content, particle size 100-150 mesh); product performance was tested according to the following methods:
[0039] Bending strength: According to GB / T 9341, a sample is cut from the product and a three-point bending test is performed to determine the bending strength;
[0040] Water resistance: The product is injected with 90℃ hot water and left to stand until the water cools to room temperature. Observe whether the product softens, leaks, or deforms, and record the time when leakage begins (the upper limit of the test is 120 min; if there is no leakage after 120 min, it is recorded as "≥120 min").
[0041] Drop test: Drop the product freely from a height of 1.0 m onto a cement surface and observe for any damage.
[0042] Degradation performance: After the product is crushed and buried in the soil of the natural environment, the time for complete degradation is recorded;
[0043] Bio-based content: determined according to ASTM D6866-22 Method B (AMS).
[0044] Example 0
[0045] This embodiment provides a bamboo powder shallow dish with the following raw material ratio (mass percentage): 35% wheat gluten and 65% bamboo powder (of which 30% is coarse bamboo powder of 20-60 mesh and 35% is fine bamboo powder of 200-500 mesh, with a coarse to fine particle mass ratio of approximately 1:1.2).
[0046] The preparation steps are as follows:
[0047] S1. First, premix the gluten powder with fine bamboo powder accounting for 30% of the total bamboo powder to form a masterbatch. Then, mix the masterbatch with the remaining bamboo powder and stir in a dry state for 5 minutes to obtain a mixed powder.
[0048] S2. Add 40℃ warm water to the mixed powder while stirring. The atomized particle size is about 30 μm. Spray it in one go until the moisture content of the material is 22%. After spraying, continue stirring for half an hour and let it stand for 15 minutes to ferment.
[0049] S3. Preheat the mold to 120℃, add the measured material into the shallow mold and press it to shape. The forming pressure (press pressure) is 100 tons.
[0050] S4. Heat and cure at 160℃ for 60 seconds, then unmold smoothly with a smooth surface;
[0051] S5. First, dry with hot air at 65℃ to a moisture content of about 10%, then dry with hot air at 95℃ to a moisture content of 5%. After inspection, packaging, and sterilization, the finished bamboo powder shallow dish is obtained.
[0052] Product performance: Dense and smooth surface, no powder shedding; flexural strength 18 MPa, impact strength 2.9 kJ / m 2 The yield rate is less than 60%; after soaking in 90℃ hot water for about 60 minutes, leakage begins along the pores; after a drop of 1.0 m, the sample cracks and breaks; after being buried in natural soil for about 90 days, it completely degrades; the bio-based content is 100%.
[0053] Example 1
[0054] This embodiment provides a bamboo powder shallow dish with the following raw material ratio (mass percentage): 35% wheat gluten and 65% bamboo powder (of which 30% is coarse bamboo powder of 20-60 mesh and 35% is fine bamboo powder of 200-500 mesh, with a coarse to fine particle mass ratio of approximately 1:1.2).
[0055] The preparation steps are as follows:
[0056] S1. First, premix the gluten powder with fine bamboo powder accounting for 30% of the total bamboo powder to form a masterbatch. Then, mix the masterbatch with the remaining bamboo powder and stir in a dry state for 5 minutes to obtain a mixed powder.
[0057] S2. Add 40℃ warm water to the mixed powder while stirring. The atomized particle size is about 30 μm. Spray in 3 intermittent sprays. Continue stirring for 60 s after each spray until the material moisture content is 22%. After spraying, let it stand and ferment for 15 min. The material is in a soft state that can be formed into a ball and can be easily crushed.
[0058] S3. Preheat the mold to 120℃, add the measured material into the shallow mold and press it to shape. The forming pressure (press pressure) is 100 tons.
[0059] S4. Heat and cure at 160℃ for 60 seconds, then unmold smoothly with a smooth surface;
[0060] S5. First, dry with hot air at 65℃ to a moisture content of about 10%, then dry with hot air at 95℃ to a moisture content of 5%. After inspection, packaging, and sterilization, the finished bamboo powder shallow dish is obtained.
[0061] Product performance: Dense and smooth surface, no powder shedding; flexural strength 28 MPa, impact strength 4.2 kJ / m 2 The yield rate is 98%; it does not leak or deform after soaking in 90℃ hot water for 2 hours; it is undamaged after a 1.0 m drop; it completely degrades after being buried in natural soil for about 90 days; and it has a 100% bio-based content.
[0062] Example 2
[0063] This embodiment provides a bamboo powder shallow dish with the following raw material ratio (mass percentage): 25% gluten powder, 70% bamboo powder (of which 30% is coarse bamboo powder of 20-60 mesh and 40% is fine bamboo powder of 200-500 mesh, with a mass ratio of coarse to fine particles of approximately 1:1.5), and 5% peach gum powder (120 mesh).
[0064] The preparation steps are as follows:
[0065] S1. First, premix the gluten powder, peach gum powder and fine bamboo powder accounting for 20% of the total bamboo powder to form a masterbatch. Then, mix the masterbatch with the remaining bamboo powder and stir in a dry state for 5 minutes to obtain a mixed powder.
[0066] S2. Add 40℃ warm water to the mixed powder while stirring. The atomized particle size is about 30 μm. Spray in 3 intermittent sprays. Continue stirring for 60 s after each spray until the material moisture content is 22%. After spraying, let it stand and ferment for 15 min. The material is in a soft state that can be formed into a ball and can be easily crushed.
[0067] S3. Preheat the mold to 120°C, add the measured material into the shallow mold and pressurize it to shape it. The forming pressure is 100 tons.
[0068] S4. Heat and cure at 160℃ for 60 seconds, then unmold smoothly with a smooth surface;
[0069] S5. First, dry with hot air at 65℃ to a moisture content of about 10%, then dry with hot air at 95℃ to a moisture content of 5%. After inspection, packaging, and sterilization, the finished bamboo powder shallow dish is obtained.
[0070] Product performance: flexural strength 25 MPa, yield 98%; compared with Example 1, toughness is significantly improved, and impact strength is increased from 4.2 kJ / m. 2 Increased to 5.6 kJ / m 2 It can withstand a 1.0 m drop without damage; it does not leak or deform after being soaked in 90℃ hot water for 2 hours; it completely degrades after being buried in natural soil for about 100 days; and it has a 100% bio-based content.
[0071] Example 3
[0072] This embodiment provides a straw-based lunchbox with the following raw material ratio (by weight): 30% wheat gluten powder, 60% wheat straw powder (a mixture of 40-80 mesh coarse particles and 300-500 mesh fine particles in a weight ratio of 1:4), and 10% peach gum powder (120 mesh).
[0073] The preparation steps are as follows:
[0074] S1. Premix 1 / 4 of the total amount of wheat gluten and peach gum powder into fine-grained straw powder to form a masterbatch, and then mix it with the remaining straw powder in a dry state for 6 minutes.
[0075] S2. Add 30℃ warm water in 4 intermittent sprays while stirring. Stir for 90 seconds after each spray until the material moisture content is 25%. Let it stand and ferment for 20 minutes until the material is soft and can be clumped and dispersed.
[0076] S3. Preheat the mold to 130℃, meter and feed the material, and set the molding pressure to 100 tons.
[0077] S4. Keep warm at 150℃ for 90 seconds, then unmold.
[0078] S5. First, dry with hot air at 60℃ to a moisture content of about 12%, then dry with hot air at 100℃ to a moisture content of 4%. After inspection, packaging, and sterilization, the finished lunch box is obtained.
[0079] Product performance: flexural strength 22 MPa, impact strength 5.2 kJ / m 2 The yield rate is 97%; the toughness is significantly improved, and it is undamaged after a 1.0 m drop; it does not leak after soaking in 90℃ hot water for 2 hours; it completely degrades after being buried in natural soil for about 100 days; and it has a 100% bio-based content.
[0080] Example 4
[0081] This embodiment provides a bamboo powder straw with the following raw material ratio (mass percentage): 35% wheat gluten and 65% bamboo powder (100 mesh to 400 mesh).
[0082] The preparation steps are as follows:
[0083] S1. Mix gluten powder and bamboo powder in dry state for 5 min to obtain mixed powder;
[0084] S2. Add 45℃ warm water in two intermittent sprays while stirring until the material moisture content is 28%, then let it stand and proof for 10 minutes.
[0085] S3. The material is fed into the screw extruder, extruded and cured into a tubular preform, and then cut off and dehydrated by hot air after extrusion.
[0086] S4. First, dry with hot air at 70℃ to a moisture content of about 10%, then dry with hot air at 90℃ to a moisture content of 5%. After inspection, packaging, and sterilization, the finished straw is obtained.
[0087] Product performance: flexural strength 26 MPa, yield 96%; does not soften or disintegrate after soaking in drinking water at 60℃ for 2 hours; completely degrades after being buried in natural soil for about 90 days; 100% bio-based content.
[0088] Comparative Example 1
[0089] This comparative example uses the same raw material ratio as Example 1, except that step S2 is changed to pouring all the water at once and then stirring (not spraying).
[0090] Results: Wheat protein powder rapidly agglomerated into unevenly sized clumps, which could not be dispersed even after 15 minutes of stirring; the interior of the clumps was dry powder. After molding, the product showed localized unbonded powder spots, uneven strength, a flexural strength of only about 12 MPa, and an impact strength of about 2.0 kJ / m. 2 After being injected with 90℃ hot water, it began to leak from the powder spots in about 30 minutes. It cracked along the powder spots after falling 1.0 m, resulting in severe powder shedding and a yield of less than 60%.
[0091] Comparative Example 2
[0092] This comparative example uses the same raw material ratio and steps S1 to S4 as Example 1. The difference is that in step S5, a one-stage hot air drying process at 100°C is used to dry the product to a moisture content of 5%.
[0093] Results: The product surface hardened and shrank first, hindering internal moisture migration. Approximately 20% of the products exhibited surface cracking or warping deformation, resulting in a yield of only about 80%. The flexural strength of the uncracked samples was approximately 26 MPa. In contrast, Example 1, which employed a two-stage drying process, achieved a cracking deformation rate of less than 2% and a yield of 98%.
[0094] Comparative Example 3
[0095] This comparative example uses the same raw material ratio and steps as Example 1, except that the maturation temperature in step S4 is 110°C.
[0096] Results: The protein curing was insufficient, resulting in a product flexural strength of only about 18 MPa and an impact strength of about 3.0 kJ / m. 2 The product in Example 1 has poor water resistance and begins to leak and soften after being injected with 90°C hot water for about 20 minutes; while the product in Example 1 has a bending strength of 28MPa and does not leak after being soaked in 90°C hot water for 2 hours.
[0097] Comparative Example 4
[0098] The difference between this comparative example and Example 1 lies in the raw material ratio (mass percentage): 20% wheat gluten and 80% bamboo powder. The specifications of the remaining raw materials and the preparation steps are exactly the same as in Example 1.
[0099] Results: The product's flexural strength was only 8 MPa, and it experienced severe surface powdering; it began to leak and disintegrate approximately 10 minutes after being injected with 90℃ hot water; and it shattered upon a 1.0 m drop. Although its degradation period was shortened to approximately 60 days, the product no longer possessed the expected performance characteristics of tableware and had no practical value.
[0100] Comparative Example 5
[0101] The difference between this comparative example and Example 1 lies in the raw material ratio (mass percentage): 70% wheat gluten and 30% bamboo powder. The specifications of the remaining raw materials and the preparation steps are exactly the same as in Example 1.
[0102] Results: Defects such as blistering and pitting appeared on the product surface, reducing the yield to about 55%; although the product's bending strength reached 30 MPa, the blistering defects became weak points for leakage, and leakage occurred from the blistering points after soaking in 90℃ hot water for about 40 minutes; and due to the high protein content and dense structure, the degradation cycle was extended to about 150 days, while the raw material cost increased significantly, and the product had a distinct burnt protein smell.
[0103] Comparative Example 6
[0104] The difference between this comparative example and Example 1 is that all the bamboo powder used is a single coarse particle size of 20-60 mesh, without any fine particle size added. The preparation steps are exactly the same as in Example 1.
[0105] Results: The product's bending strength was 17 MPa, the surface was rough and there was obvious powder shedding; after soaking in 90℃ hot water for about 50 minutes, leakage began to occur along the pores.
[0106] Comparative Example 7
[0107] The difference between this comparative example and Example 1 is that soy protein isolate (90% protein content) is used instead of wheat gluten, and the raw material ratio (mass percentage) is 35% soy protein isolate and 65% bamboo powder (coarse and fine particle size blended as in Example 1). The specifications of the remaining raw materials and the preparation steps are exactly the same as in Example 1.
[0108] Results: The product's flexural strength is only about 15 MPa, and its impact strength is about 2.5 kJ / m. 2 After being injected with 90℃ hot water, leakage began to occur in about 40 minutes, the surface became sticky, and the product had a distinct beany smell; some samples were damaged when dropped from 1.0 m; the yield rate was about 90%.
[0109] Comparative Example 8
[0110] The difference between this comparative example and Example 1 is that wheat flour (protein content of approximately 12%) is used instead of wheat gluten, and the raw material ratio (mass percentage) is 35% wheat flour and 65% bamboo flour (coarse and fine particle size blending is the same as in Example 1). The specifications of the remaining raw materials and the preparation steps are exactly the same as in Example 1.
[0111] Results: The product's flexural strength is only about 10 MPa, and its impact strength is about 1.5 kJ / m. 2 The surface shows significant powder shedding; the starch component, after gelatinization, re-swells upon contact with water, and leaks and disintegrates within approximately 15 minutes after being injected with 90℃ hot water; furthermore, the high starch content makes the product prone to moisture absorption and mold growth during storage, significantly shortening its shelf life; it breaks upon a 1.0 m drop. Increasing the amount of wheat flour to increase protein content further increases the starch content, further deteriorating water resistance and mold resistance, failing to fundamentally solve the problem.
[0112] The main performance test results of each embodiment and the comparative example are compared in Table 1 below.
[0113] Table 1. Main performance test results of each embodiment and comparative example
[0114]
[0115] As can be seen from the comparison of the above examples and comparative examples, the ratio of wheat gluten powder to natural plant fiber powder is crucial to the performance of the product. When the proportion of wheat gluten powder is less than 25% (Comparative Example 4), the product strength and water resistance deteriorate sharply, rendering it unusable. When the proportion of wheat gluten powder is higher than 60% (Comparative Example 5), the material processing performance deteriorates, the yield drops significantly, and the degradation cycle is significantly prolonged, leading to increased costs. Only within the ratio range defined by this invention can the product simultaneously achieve a balance between high strength (flexural strength of 22 MPa~28 MPa, far exceeding the 8 MPa~17 MPa of low wheat gluten powder solutions outside the ratio range), long water resistance time (≥120 min), and short degradation cycle (approximately 90 days~100 days). This comprehensive performance effect is unattainable by solutions outside the ratio range, achieving unexpected technical results. Furthermore, the comparison between Examples 2 and 3 and Example 1 shows that the impact strength of the product increased from 4.2 kJ / m after adding natural gum powder. 2 Increased to 5.2 kJ / m 2 ~5.6kJ / m 2 This verified the technical effectiveness of the optimal toughening scheme using natural resin.
[0116] Specifically, Comparative Examples 7 and 8 replaced the gluten powder of the present invention with soybean protein and wheat flour, respectively, which are already used as adhesives for disposable tableware in the prior art, under the same formulation and process conditions. The results showed that the flexural strength and water resistance of the soybean protein solution were significantly inferior to those of the gluten powder solution of the present invention. The wheat flour solution, due to its low effective protein content and the swelling of starch components upon contact with water, had a flexural strength of only about 10 MPa and a water resistance of only about 15 min, and was also prone to moisture absorption and mold growth. It is evident that the selection of wheat protein (gluten powder) as a plant protein adhesive is not a conventional equivalent substitution by those skilled in the art, and this selection brings significantly superior technical effects to the present invention compared to the prior art. At the same time, the preferred schemes such as segmented spray humidification and static proofing, two-stage drying, suitable maturation temperature range, and coarse and fine particle size compounding also specifically solved the technical problems of uneven humidification, drying cracking, insufficient water resistance, and poor density in the implementation of the basic scheme, significantly improving product performance and yield.
[0117] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A biodegradable disposable tableware, characterized in that, It is made from all-plant-based raw materials containing binder components and fiber components; the binder component is wheat protein powder, and the fiber component is natural plant fiber powder; by mass percentage, the wheat protein powder accounts for 25% to 60% of the raw materials, and the natural plant fiber powder accounts for 40% to 75% of the raw materials; the raw materials do not contain chemically synthesized binders, waterproofing agents, plasticizers, or preservatives.
2. The disposable tableware according to claim 1, characterized in that, The wheat gluten powder is wheat gluten powder, with a protein content of not less than 75% and a particle size of 80-200 mesh.
3. The disposable tableware according to claim 1, characterized in that, By weight percentage, the wheat protein powder accounts for 30% to 45% of the raw materials, and the natural plant fiber powder accounts for 55% to 70% of the raw materials.
4. The disposable tableware according to claim 1, characterized in that, The natural plant fiber powder is selected from one or more of bamboo powder, wood powder, straw powder, rice husk powder, wheat bran powder, bagasse powder, and coconut shell powder, and the particle size of the natural plant fiber powder is 20 mesh to 500 mesh.
5. The disposable tableware according to claim 4, characterized in that, The natural plant fiber powder is composed of coarse-grained fiber powder and fine-grained fiber powder. The particle size of the coarse-grained fiber powder is 20 mesh to 100 mesh, and the particle size of the fine-grained fiber powder is 100 mesh to 500 mesh. The mass ratio of the two is 1:5 to 1:
1.
6. The disposable tableware according to any one of claims 1 to 5, characterized in that, The raw materials also include 5% to 15% natural gum powder, which is gum arabic powder and / or gum arabic powder.
7. A method for preparing disposable tableware according to any one of claims 1 to 6, characterized in that, Includes the following steps: S1. Ingredient mixing: Weigh the wheat protein powder, natural plant fiber powder and optional natural gum powder according to the ratio, and mix them evenly in a dry state to obtain a mixed powder. S2. Spray humidification: Water is sprayed onto the mixed powder while stirring until the moisture content of the material is 15%~30%; S3. Compression molding: The humidified material is metered and added into the product mold and pressed to shape it. The molding pressure is 50~150 tons. S4. Heating and cooking: Hold at 130℃~160℃ for 60 s~120 s; S5. Drying: After demolding, dry with hot air until the product moisture content is 3%~6%, and the finished product is obtained.
8. The method according to claim 7, characterized in that, In step S2, the spray humidification is performed intermittently in 2 to 4 times. After each spray, stirring is continued for 30 to 120 seconds before the next spray. After the spray humidification is completed, stirring is continued for 20 to 30 minutes, and the material is allowed to stand and ferment for later use.
9. The method according to claim 8, characterized in that, In step S2, the atomized particle size of the water used for spraying is no greater than 50 μm, and the water temperature is 20℃~60℃.
10. The method according to claim 7, characterized in that, In step S4, the aging temperature is 145℃~150℃.